The impact of transcutaneous electrical nerve stimulation on COVID-19 patients, especially those admitted to the intensive care unit - Alipour, Rasoul; Mikaeili, Fariba (International Journal of Advances in Medicine, 2020)
Physiotherapy and early mobilization are necessary to treat COVID-19 patients. Physiotherapy is effective in strengthening of respiratory muscles, reduction of inflammation, and enhanced immune function in COVID-19 patients. Physiotherapy can relieve various symptoms of COVID-19. TENS (Transcutaneous Electrical Nerve Stimulation) is a kind of physiotherapy that uses electric current to activate nerves for therapeutic reasons. It passes electrical currents across the intact surface of the skin to activate underlying nerves. There are many studies that shown that TENS can alleviate dyspnea and lung function and improve FEV1 in patients with COPD and asthma, which is a more common complication in COVID-19 patients. TENS is effective in the treatment of muscle weakness and able to preserve protein synthesis in muscle in admitted patients, especially those admitted to ICU. Because of those reasons mentioned in the article, we recommend to investigate TENS effects on COVID-19 patients.